Can positive and self-transcendent emotions promote pro-environmental behavior?. (December 2021) - Zelenski, John M.; Desrochers, Jessica E.
Abstract: Many scholars have suggested that people could improve their well-being by developing closer connections with nature and that this would also promote the sustainable behaviors needed to address climate change. Research generally corroborates this idea, but few studies have examined the more specific hypothesis that positive emotions (caused by nature or otherwise) can directly influence pro-environmental behaviors. In particular, self-transcendent emotions such as awe, compassion, and gratitude can be prompted by nature, and they seem to foster prosocial behaviors. Most pro-environmental behaviors are also prosocial; they require cooperation and they benefit others. Some recent studies suggest that self-transcendent emotions can cause pro-environmental behavior, although results are mixed overall. We identify strategies for future research to resolve these inconclusive suggestions.